A dietary pattern of frequent plant-based foods intake reduced the associated risks for atopic dermatitis exacerbation: Insights from the Singapore/Malaysia cross-sectional genetics epidemiology cohort - Lim, Jun Jie; Kavita, Reginald *; Say, Yee How*; Liu, Mei Hui; Chew, Fook Tim (BMC (Springer Nature), 2023)
Background: The prevalence of atopic dermatitis (AD) has been increasing in recent years, especially in Asia. There is growing evidence to suggest the importance of dietary patterns in the development and management of AD. Here, we seek to understand how certain dietary patterns in a Singapore/Malaysia population are associated with various risks of AD development and exacerbation.